2010
DOI: 10.1111/j.1464-5491.2010.03061.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors associated with use of continuous glucose monitoring

Abstract: Aims To identify psychosocial factors associated with the use of continuous glucose monitoring by adults with Type 1 diabetes.Methods Twenty adult patients (aged 45 AE 15 years, diabetes duration 25 AE 19 years, 50% female) followed at our site in the multi-centre Juvenile Diabetes Research Foundation continuous glucose monitoring trial were divided into three groups: Glycated haemoglobin (HbA 1c ) Responders who demonstrated an improvement in glycaemic control with continuous glucose monitoring (baseline HbA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
147
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(159 citation statements)
references
References 22 publications
9
147
1
2
Order By: Relevance
“…For example, although not specifically predictive of frequency of use, other studies have found relations between better outcomes using CGM and patient-report of greater motivation for glycemic control, better coping resources, a better understanding of how to use CGM data, and greater family support, suggesting the opposites of all of these could be additional barriers to use. 11,42 Interventions targeting more frequent CGM use are few. There is 1 trial (NCT01472159) currently under way in the United States that is investigating the impact of a CBT+MI focused intervention on increasing CGM use among adolescents.…”
Section: Real-time Cgmmentioning
confidence: 99%
“…For example, although not specifically predictive of frequency of use, other studies have found relations between better outcomes using CGM and patient-report of greater motivation for glycemic control, better coping resources, a better understanding of how to use CGM data, and greater family support, suggesting the opposites of all of these could be additional barriers to use. 11,42 Interventions targeting more frequent CGM use are few. There is 1 trial (NCT01472159) currently under way in the United States that is investigating the impact of a CBT+MI focused intervention on increasing CGM use among adolescents.…”
Section: Real-time Cgmmentioning
confidence: 99%
“…The 18 studies included in this review consist of 5 qualitative studies [40][41][42][43][44], 5 experimental studies [31][32][33][34][35], 3 observational studies [28][29][30], 4 cross-sectional studies [36][37][38][39] and 1 mixed methods [45]. Five of the studies were smaller samples drawn from parent clinical trials [29,32,38,40,41].…”
Section: Resultsmentioning
confidence: 99%
“…Higher relationship quality is associated with lower diabetes-related distress, better quality of life, and greater adherence to the medical regimen [8][9][10][11]. Partner encouragement may also help individuals with T1D get more benefit from CGM [12]. A recent T2D-focused study found positive effects on glycemic control for a couples-based health intervention [13].…”
Section: Diabetes and The Role Of Partnersmentioning
confidence: 99%